Pembelajaran SBdP Berbasis Pertanian Industrial dengan Model Project Based Learning (PjBL) Projek Kolase Untuk Meningkatkan Kreativitas Siswa - Marice, Ika Elis; Wicaksono, Iwan; Sudarti, Sudarti; Wuryaningrum, Rusdhianti (WASIS : Jurnal Ilmiah Pendidikan, 2025)
This study aims to improve the creativity of grade 1 students through SBdP learning based on industrial agriculture with a collage project at Papringan 02 Elementary School in Klakah District. The type of research used is quantitative research. Where the research design uses an experimental research type. This research was conducted at Papringan 02 Elementary School, Papringan Village, Klakah District, Lumajang Regency in the odd semester of the 2023 academic year. Sampling in this study used a purposive sampling technique. The independent variable in this study is the Project Based Learning (PjBL) learning model, while the dependent variable is students' ability to make inorganic collages. The data collection procedure involves several methods, including pretest-posttest tests, assignments, and observations. The data analysis technique in this study uses quantitative data analysis techniques. Based on the results of the paired sample t-test, it is known that the Sig. (2-tailed) score is 0.002 <0.05. Therefore, the null hypothesis (Ho) can be rejected, and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that there is a significant difference in the average value between the results of the Pretest and Posttest. The application of learning with collage projects in SBdP learning has a positive influence in improving students' learning creativity at Papringan 02 Elementary School, Klakah District, Lumajang Regency.